The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1016/0014-5793(96)00578-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical effects on catalytic function produced by amino acid substitutions at Asp804 and Asp808 of the al isoform of Na,K‐ATPase

Abstract: At two intramembrane carboxyl-containing amino acids of the sheep al isoform of Na,K-ATPase (Aspso and Aspass), both charge-conserving (Asp to Glu) and charge-deleting (Asp to Asn, Leu and Ala) replacements were made and the altered enzymes studied. Nucleotide changes encoding the amino acid substitutions were placed in a cDNA encoding a ouabainresistant enzyme (sheep al RD) and the encoded enzymes were expressed in ouabain-sensitive HeLa cells. Transfections with cDNAs carrying all As so4 L carrying AspsesAla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…It has previously been shown that replacement of Asp 804 with Ala, Leu, Asn, or Glu, and Asp 808 with Ala, Leu, or Asn results in proteins that are unable to support cell growth when expressed in HeLa or COS cells (18,21,25,27). Thus, these substituted proteins could not be characterized in these expression systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that replacement of Asp 804 with Ala, Leu, Asn, or Glu, and Asp 808 with Ala, Leu, or Asn results in proteins that are unable to support cell growth when expressed in HeLa or COS cells (18,21,25,27). Thus, these substituted proteins could not be characterized in these expression systems.…”
Section: Resultsmentioning
confidence: 99%
“…In this system ouabain binding at nanomolar concentrations of [ 3 H]ouabain was used to probe the exogenous protein without interference from the endogenous mouse Na,KATPase. Ouabain binding is an indication of the enzyme's overall structural integrity and under appropriate conditions provides information on the enzyme localization (20,27). Furthermore, the kinetics of ouabain binding depend on the different conformational states that the Na,K-ATPase can assume (38 -41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the former enzyme have shown that the carboxyl-selective reagent 4-(diazomethyl)-7-(diethylamino)-coumarin disrupts K ϩ and Na transport (30,31,33,43). Taken together, these findings imply that the M5 glutamyl residue is directly involved in transport by the mammalian Na -ATPase, both of which are required for high affinity cation binding and transport (30,31,33,39,41,43). Unlike its homologues, however, Asp-730 of the H ϩ -ATPase is not detectably involved in transport, since it can be replaced by Ala (as part of an R695A/ D730A double mutant) with little or no effect on ATP hydrolysis or ATP-dependent proton pumping.…”
Section: Mechanism Of Proton Transport: Role Of Charged Residues In Mmentioning
confidence: 98%
“…For example, most of the extramembraneous regions of the Na ϩ /K ϩ -ATPase can be removed by proteolytic digestion while the remaining portion of the enzyme maintains its ability to bind and occlude K ϩ (10). Furthermore, mutagenesis studies have identified a number of amino acid residues within M4, M5, and M6 of the Na ϩ /K ϩ -ATPase that appear to be critical for cation binding (11)(12)(13)(14). These residues are in general polar, and most are negatively charged.…”
mentioning
confidence: 99%